Optimalisasi Hasil Perikanan Melalui Pembuatan Abon Ikan Mujair dengan Penambahan Nangka Muda di Desa Kedungpeluk, Kecamatan Candi, Sidoarjo - Rovino Achmad Hidayat; Nadia Iffatul Arifah; Ellecia Pricillia Siahaan; Shafa Azzahra Ramadeandra; Ririn Anggraini; Muhammad Mahar Iman Wijaya; Dewi Puspa Arum (Jurnal Pelayanan Masyarakat, 2024)
This socialisation activity aims to optimise the utilisation in processing fishery products through making shredded tilapia with young jackfruit as an additional ingredient in the Kedungpeluk Village area, which is located in Candi District, Sidoarjo Regency. The method used was observation, interview, preparation of work programme and practice in making shredded tilapia. The activity began with socialisation to the PKK women's group to increase understanding and skills in processing tilapia into shredded fish. The use of young jackfruit is a form of innovation in developing local food potential and is an effort to diversify food which is a diversity of products consumed and improve the value of fibre in processed meat such as shredded which has low fibre. This socialisation activity is expected to be able to provide direction to the Empowerment and Family Welfare (PKK) women's group in Kedungpeluk Village, Candi Subdistrict, Sidoarjo Regency to gain knowledge and skills in processing tilapia and young jackfruit into processed products